Distribution Study of Corypha utan Lamk. From Herbarium Bogorienses Specimens and the Conservation Areas in East Java - Irawanto, Rony (Proceeding International Conference on Global Resource Conservation, 2013)
Species of palms widely used as building materials, household, handycrafts, food resources, oil sources, energy sources, medicinal plants, ornamental plants and environmental services plant. Species of palm that native and unique is Corypha. Palm (Arecaceae) in Indonesia has a high biodiversity so that conservation efforts are needed. Purwodadi Botanic Garden as ex-situ conservation organizations has a palm collection of 358 specimens from 93 species, including Corypha. As many palm species, Corypha also has usefull, so it can be use and take by the community. According that Corypha have slow growth and regeneration only depends from seed, with the kind of seed plants only once flowering-fruiting after then die (hepaxantic). So this research needs to be done. This study aims to determine the distribution of Corypha based on specimens in the Herbarium Bogoriensis (BO) and the conservation areas, for example, selected Baluran Natinal Park and Sempu Conservation Area (as representative of in-situ conservation) and the Purwodadi Botanic Garden (as representative of ex-situ conservation). Descriptive study was conducted based on literature references, study specimens in the herbarium and direct observations in the field. The result in Herbarium Bogoriensis recorded 85 specimens Corypha with C. utan most collected (57) and the dominant in Java. In Baluran National Park listed 187 tag point distribution of C. utans on 4 track (Batangan-Bekol, Bekol-Bama, Sumber Manting and Curah Udang). In Sempu Conservation Area recorded 32 tag point distribution of C. utan on track from Waru-waru to Telaga Lele. Meanwhile, the Purwodadi Botanic Garden has 2 plants (living collection) C. umbraculifera and C. utan that have 55 years old and only 1 specimen (herbarium collections) from C. umbraculifera. So that it is necessary to do conservation efforts, especially C. utan on insitu or exsitu conservation, or both of them.Â Keywords: Baluran National Park, Corypha, distribution, Herbarium Bogoriensis, Purwodadi Botanic Garden, Sempu Conservation Area